2003
DOI: 10.1073/pnas.1231332100
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge systems for sustainable development

Abstract: The challenge of meeting human development needs while protecting the earth's life support systems confronts scientists, technologists, policy makers, and communities from local to global levels. Many believe that science and technology (S&T) must play a more central role in sustainable development, yet little systematic scholarship exists on how to create institutions that effectively harness S&T for sustainability. This study suggests that efforts to mobilize S&T for sustainability are more likely to be effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
2,167
0
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,842 publications
(2,365 citation statements)
references
References 26 publications
25
2,167
0
26
Order By: Relevance
“…Previous research has suggested that the concept of "boundary work" provides one potentially powerful leverage point for designing research programs that better link knowledge with action for sustainability (Cash et al 2003). "Boundary work" signifies the processes through which the "research community organizes its relations with the worlds of action and policy making" (Hellstrom and Jacob 2003, 235) on the one hand, and with practice-based and other forms of knowledge on the other.…”
Section: Boundary Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that the concept of "boundary work" provides one potentially powerful leverage point for designing research programs that better link knowledge with action for sustainability (Cash et al 2003). "Boundary work" signifies the processes through which the "research community organizes its relations with the worlds of action and policy making" (Hellstrom and Jacob 2003, 235) on the one hand, and with practice-based and other forms of knowledge on the other.…”
Section: Boundary Workmentioning
confidence: 99%
“…"Boundary work" signifies the processes through which the "research community organizes its relations with the worlds of action and policy making" (Hellstrom and Jacob 2003, 235) on the one hand, and with practice-based and other forms of knowledge on the other. Originally developed to help understand efforts to demarcate "science" from "non-science" (Gieryn 1983;Evans 2005), the idea of boundary work has since been applied to the interface between science and policy (Jasanoff 1990;Guston 2001) and, more broadly, to the activities of organizations that seek to mediate between knowledge and action (Cash et al 2003).…”
Section: Boundary Workmentioning
confidence: 99%
“…As a result, increasing attention is currently being paid to developing environmental governance systems that incorporate different perspectives of nature and forms of environmental knowledge. Environmental scholars and policymakers now explore processes of coproduction of knowledge (ICSU 2005, Berkes 2008), knowledge articulation (Galopin and Vessuri 2006), knowledge integration (Raymond et al 2010), knowledge systems (Cash et al 2003), and transdisciplinarity (Pregernig 2006), among others.…”
Section: Cognitive Justice Cultural Revitalization and Well-being Fmentioning
confidence: 99%
“…Evidence from different environmental policy and governance settings indicates that these organizations can serve as clearing houses for information, foster conflict resolution, and, where supported by legislation, build the legitimacy and credibility needed to encourage behavioral change (Cash et al 2003;Huitema and Turnhout 2009;Crona and Parker 2012). To achieve these potential benefits, however, boundary organizations require cultivation, experience, and involvement from stakeholders at higher and lower levels of governance.…”
Section: Engage Boundary Organizations and Informal Networkmentioning
confidence: 99%
“…It is now widely accepted that scientific knowledge alone is not sufficient for dealing with complex environmental issues (Lejano and Ingram 2009). At the same time, the gulf that often exists between ''decision makers'' and scientists can be wide (Cash et al 2003). Recognition of this fact accounts for the enormous amount that is being written about strategies to improve science-policy interaction (e.g., Roux et al 2006;Karl et al 2007;Pielke 2007;Ascher et al 2010;Kasperson and Berberian 2011).…”
Section: Introductionmentioning
confidence: 99%